Dever do Estado e direito do cidadão: as políticas públicas no governo varguista no Espírito Santo (1930-1945) - Grazziotti, Marinete Simões (2006)
The present study has as its main objective to analyze public policies geared towards the less privileged, implemented in the State of Espírito Santo between 1930 and 1945 under the Vargas’ state control. In order to carry out this analysis, we focus on the areas where these policies worked, with an emphasis on the health and educational sectors. As documental sources, we used laws, decrees, speeches, newspapers and messages by the Presidents of the State during that period: Punaro Bley and Jones Santos Neves. By analyzing the public policies destined to the needy, we are investigating, at the same time, how the Vargas’ State perceived poverty and social exclusion. It is understood that, with the implementation of public actions geared to support the excluded levels of society, the Brazilian State takes over a clear assistentialist posture, intending, in that manner, to solve the problem of generalized poverty.